A Vocation of Holiness: A Practitioner Rereads the Doctrinal Standards of the British Methodist Church - Turner, Philip Stanley (Wesley and Methodist studies, 2021)
There are many ways to source a theology of the Methodist Church of Great Britain. This article argues that a rooted, engaging, and dynamic British Methodist theology can be sourced from its doctrinal standards. The doctrinal standards are not only the legal basis of the church, but also an inspiration for Methodists seeking to understand their identity and purpose in our complex twenty-first-century context. The article shows how the doctrinal standards call British Methodists to a vocation of holiness and how John Wesley's forty-four Sermons and Explanatory Notes upon the New Testament illuminate this vocation. Research is highlighted that points to how presbyters can empower Methodists to embark on a journey to explore Methodism's "special vocation".